ANALISIS KEPUASAN MAHASISWA TERHADAP LAYANAN KESEHATAN POLIKLINIK ASY-SYIFAA DAN IMPLIKASINYA UNTUK PENINGKATAN FASILITAS KESEHATAN DI UIN ALAUDDIN MAKASSAR - Rahmah, Nur; Rini Jusriani; Abd. Majid HR Lagu; Kahfi, Muh (Universitas Islam Negeri Alauddin Makassar, 2025)
The use of health services is important to maintain and improve health, prevent the onset or worsening of disease, cure disease, and restore health conditions. This study aims to see the use of polyclinics and satisfaction of students of the Public Health Study Program at the UIN Alauddin Makassar campus. This type of research is quantitative through a cross-sectional approach. The sample size in this study was 229 respondents who were students of the Public Health Study Program. This study was conducted on September 20-25, 2024 with a sample collection method by giving questionnaires to students of the Public Health Study Program. Based on the results of the univariate analysis test obtained from 30 respondents who utilized health facilities 2 times or more than 2 visits, it was found that the majority of respondents were satisfied with each variable, including the tangible variable 21 people (70.0%), reliability 22 people (73.3%), responsiveness 21 people (70.0%), assurance 22 people (73.3%), and empathy 21 people (70.0%). Meanwhile, students who do not utilize the polyclinic at UINAM, the majority of the reasons are that they have never been sick, are more comfortable using health services outside the campus, and prefer to consult with a private doctor or service clinic. Therefore, suggestions and input from UINAM students are obtained, namely that the campus polyclinic needs to improve socialization regarding the service flow and its advantages so that it is better known by students. In addition, it is necessary to improve the quality of service by ensuring that staff are friendlier and more thorough, completing the necessary medical equipment, and improving the comfort of the waiting room and accessibility of health facilities. This is expected to encourage students to trust and choose health services on campus more.